ChemInform Abstract: The Mercury‐Richest Europium Amalgam Eu10Hg55. Issue 22 (15th May 2015) - Tambornino, Frank; Hoch, Constantin
Abstract: Single crystals of Eu10 Hg55 are prepared by isothermal electrocrystallization under anhydrous conditions from a solution of EuI3 ·8DMF in DMF on a reactive Hg cathode (amalgamated Cu spoon, 5 V, 72 h).